Anxiety and Depression: Comparative Study between Working and Non-working Mothers (Global Journal of Human-Social Science, 2012)
Now a day the mothers are not only restricted their involvement on domestic chores procreation of children and their nurturing with family care and attention A significant number of mothers are working and they are maintaining their dual of as employee and household keeper with financial assistance to their families The working mothers are mostly in anxiety and depression regarding their method of child care as they are absentees for a long time The present study had been conducted to find out the differences in degree of felt depression and anxiety pattern of working non-working mothers A total of 60 mothers 30 working mothers 30 nonworking mothers were studied The result showed that there were significant differences in degree of depression both anxiety of working mothers group But no significant difference was noticed in case of anxiety depression pattern of non-working mothers group
Keywords: Mother; Anxiety; Depression; Child Care; household Work